DURASI DAN FREKUENSI PENGGUNAAN GAWAI TERHADAP PERKEMBANGAN SOSIAL ANAK PRA SEKOLAH DI TK ISLAM PERMATA HATI KELAPA DUA KABUPATEN TANGERANG TAHUN 2019 - Yenny Aulya; Suprihatin Suprihatin; Ririn Arantika (JKM (Jurnal Kebidanan Malahayati), 2020)
ABSTRACT Background: In 2011 there were 38% of gadget users in children aged 5 years in Indonesia and in 2013 increased to 72%. The use of devices makes children lazy to move and activities. This situation will affect the child's development both in terms of physical, motor, psychological, and social child.Objective: To identify the relationship between the duration and frequency of using a device to the social development of preschool children in the Permata Hati Hati Dua Islamic Kindergarten, Tangerang Regency in 2019.Methodology: This research is an analytic epidemiological study with cross sectional study design. The population in this study were all parents of students at the Permata Hati Kindergarten, totaling 54 people. Sampling uses total sampling. Primary data were collected using a questionnaire. Data analysis through two stages, namely univariate and bivariate using the Chi-Square test.Results: The majority of pre-school children had poor social development (55.6%), with duration of playing devices> 1 hour / day (53.7%), and frequency of use of devices> 3 days a week (55.6 %). The results of this study indicate that there is a significant relationship between the duration and frequency of use of the device to the social development of children.Conclusions : There is a relationship between the duration and frequency of the use of the device to the social development of pre-school children.            Suggestion : It is hoped that parents will be more selective in giving toys to children, especially granting permission to play devices. It is necessary to be firm and mentor from parents in providing limitations on the duration and frequency of device use by children  Keywords: Duration, frequency, device, social development, preschool children ABSTRAK Latar Belakang : Tahun 2011 terdapat 38% pengguna gawai pada anak usia 5 tahun di Indonesia dan pada tahun 2013 meningkat menjadi 72%. Penggunaan gawai membuat anak menjadi malas bergerak dan beraktifitas. Keadaan seperti ini akan mempengaruhi perkembangan anak baik dari segi fisik, motorik, psikologis, dan sosial anak.Tujuan : Untuk mengidentifikasi hubungan durasi dan frekuensi penggunaan gawai terhadap perkembangan sosial anak prasekolah di TK Islam Permata Hati Kelapa Dua Kabupaten Tangerang Tahun 2019.Metodologi : Penelitian ini merupakan penelitian epidemiologi analitik dengan  desain studi cross sectional. Populasi dalam penelitian yaitu seluruh orang tua siswa di TK Islam Permata Hati yang berjumlah 54 orang. Pengambilan sampel menggunakan total sampling. Data primer dikumpulkan dengan menggunakan kuesioner. Analisis data melalui dua tahapan yaitu univariat dan bivariat dengan menggunakan uji Chi-Square.Hasil Penelitian : Sebagian besar anak pra sekolah memiliki perkembangan sosial yang kurang baik (55,6%), dengan durasi bermain gawai > 1 jam/hari (53,7%), dan frekuensi penggunaan gawai > 3 hari dalam seminggu (55,6%). Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara durasi dan frekuensi penggunaan gawai terhadap perkembangan sosial anak.Simpulan  : Ada hubungan durasi dan frekuensi penggunaan gawai terhadap perkembangan sosial anak pra sekolah.Saran Diharapkan orang tua lebih selektif dalam memberikan mainan kepada anak,terutama pemberian izin bermain gawai.Perlu Ketegasan dan pendampingan dari orang tua dalam memberi Batasan durasi dan frekuensi penggunaan gawai oleh anak  Kata Kunci : Durasi, Frekuensi, Gawai, Perkembangan sosial, Anak Prasekolah